Identifying the most commonly occurred clinical symptoms of covid-19 patients at southern hospitals and community setting – a retrospective study - Ch, Sai Himabindu; K, Sreevani; B, Tanish; Chandaka , Madhu; B, Tejasree (Journal of Innovations in Applied Pharmaceutical Science (JIAPS), 2022)
Background: The First Case Of A Novel Coronavirus (COVID-19) Infection Was Detected In Wuhan, Fever And Respiratory Symptoms Have Been Frequently Reported In Patients Infected With This Virus. Aim: It Was Aimed To Detect The Most Commonly Occurred Clinical Symptoms Of COVID19 In Hospitals And Community Settings. Method: Patients Presenting To Southern Hospitals And Community Settings For COVID-19 Infection Were Included In The Study. Assessment Of Demographics And Background Information Of Covid-19 Infection Is Done And Next The Patients Were Questioned For 22 Symptoms And The Results Were Compared. Listing Out The Symptoms And Symptoms Status And Functionality Status Prior to The Collection Of All Data For Statistical Analysis To Represent The Results. Results: A Total Of 403 Patients With COVID-19 Positive Status Were Included In The Study. The Most Common Symptoms In The COVID-19 Positive Group Were: Cough (81.9%), Shortness Of Breath (78.7%), Sneezing (77.4%), Fever (91.4%), Headache (89.6%), Loss Of Taste (69.2%), And Muscle Pain (80.1%). Conclusion: Our Study Showed That Taste And Cough Were Important Markers In COVID-19 Infection.